KEANEKARAGAMAN JENIS BURUNG DI CAGAR ALAM PULAU DUA, BANTEN - Pertiwi, Herlina Juwita (Biosel Biology Science and Education, 2021)
Pulau Dua Nature Reserve (CA) is a conservation area and one of the Important Bird Areas (IBA), which is a habitat for various bird species. The condition of the habitat ecosystem in Pulau Dua CA is currently experiencing disturbances and damage so that biodiversity, including bird species, is disturbed. This research was conducted to determine the diversity of bird species in various habitats in Pulau Dua CA. The method used is a survey with Point Transect on the type of habitat for ponds, mangrove forests, and coastal areas. Based on the results obtained, 31 bird species from 18 families were observed that can be found in Pulau Dua CA. A total of 27 bird species are permanent residents and 4 birds are migrant species. The highest species diversity index (H ') value of the three habitat types was found in 2.62 ponds including the very good category (2.59